Life story resources in dementia care: a review. (2nd September 2014) - Kindell, Jacqueline; Burrow, Simon; Wilkinson, Ray; David Keady, John
Abstract : Purpose: – Life story work has a relatively long tradition in the caring sciences and is recognised as an important component of dementia care and practice. However, to date, there has not been a review of accessible life story resources. The paper aims to discuss these issues. Design/methodology/approach: – Following a systematic approach to identification and inclusion, 11 life story resources were reviewed to ascertain areas of commonality and divergence between the materials. Findings: – The authors were able to group the analysis under eight areas and at the end of this process, it was uncertain if life story work is a formal staff intervention or an informal activity that people with dementia and their families could engage in. Resources also varied in terms of whether the life story information was organised in a chronological way, or with topics of interest/discussion or with a combination of both. Life story evaluation and its impact on the life of the person with dementia is in need of development. Practical implications: – Across the resources the authors identified four reasons to do life story work which the authors have named as: emotional connections; interactional connections; building new connections and practical care connections. Social implications: – There was limited guidance aimed at helping people with dementia to develop and compile their own life story. Originality/value: – This paper provides new insights into the usefulness, future directions and content of life story resources in dementia care. It will be of interest to those in health and social care as well as people living with dementia.